The Conjunction Fallacy and the Debate on Human Rationality - Moro, Rodrigo (2009)
A. Tversky and D. Kahneman (1983) showed that in some contexts people tend to believe that a conjunction of events is more likely to occur than one of the events involved (a phenomenon called “conjunction fallacy”). The goal of this paper is to analyze the consequences of this phenomenon for the issue of human rationality. The key questions are as follows. Given the evidence from the conjunction fallacy experiments, are we justified to endorse some thesis on human rationality? If yes, which thesis? If not, why? The answers we give to these questions, I will argue, depends on the conception of rationality we advocate. I will then explore the consequences of the empirical evidence for three conceptions of rationality: The Standard Picture, Ecological Rationality, and the Goal Oriented View. Finally, I will compare these positions and offer a menu of philosophical options on human rationality that take into account the psychological studies in this area.